Examining the moderating role of perceived lack of facilitating conditions on household recycling intention in Kano, Nigeria - Khalil, Muhammad Salisu; Abdullah, Sabrina Ho; Abd Manaf, Latifah; Sharaai, Amir Hamzah; Nabegu, Aliyu Baba (M D P I AG, 2017)
Improper handling of household solid waste causes problems that affect public health and the environment, as well as the aesthetic nature of cities. This paper aims to determine if the theory of planned behavior (TPB), and its extended version can be used to predict household recycling intention (RI), and whether perceived lack of facilitating conditions have a moderating role on households’ RI in Nigeria. Data from a sample of 393 households from Kano metropolis Nigeria were analyzed using structural equation modeling. The result reveals that the TPB Model predicts households RI in Nigeria and explains 42% of the variance in RI. Attitude is the most important predictor of RI in the TPB model (β = 0.593, p = 0.000). However, after personal norm (PN) was added into the model, the variance in RI increases to 58% and PN becomes the most important predictor of RI in the extended TPB model (β = 0.496, p = 0.000). Perceived lack of facilitating condition was found to have a significant moderating effect on households’ RI. Finally, our findings show that providing households with recycling facilities and local collections holds great promise for improving households’ intention to recycle.